Premonitory Urges in Adults With Complicated and Uncomplicated Tourette Syndrome. (March 2014) - Eddy, Clare M.; Cavanna, Andrea E.
Most patients with Tourette syndrome (TS) report experiencing subjective bodily sensations termed premonitory urges, before they have a tic. This study investigated relationships between premonitory urges and tic severity, depression, anxiety, obsessions, compulsions, and attention problems. We also explored possible differences between patients with and without comorbid conditions. Finally, we explored whether premonitory urges impacted on perceived quality of life (QoL). One hundred adult outpatients (70 males; mean age 32 years) were recruited from a specialist TS clinic. Fifty percent exhibited comorbid diagnoses, the most common of which were obsessive-compulsive disorder (23%), attention-deficit hyperactivity disorder (15%), anxiety (6%), and depression (5%). For the entire sample, premonitory urges were significantly related to clinical symptoms, especially obsessive-compulsive symptoms and anxiety, and were significantly negatively related to QoL scores. Premonitory urges had a strong negative correlation with QoL in patients with "pure" TS (no comorbidities), while this relationship was weaker for patients with comorbid conditions, who reported stronger or more frequent premonitory urges in association with greater anxiety. These findings may imply that slightly different psychological factors drive self-reported premonitory urge ratings in patients with and without comorbidities and that the perceived influence of distressing premonitory urges on wellbeing is less important in the context of comorbid symptomatology. As premonitory urges are related to QoL, they should be taken into account during evaluation of treatment efficacy, especially in cases with "pure" TS.